Epigallocatechin gallate-loaded pH-responsive dressing with effective antioxidant, antibacterial and anti-biofilm properties for wound healing. (March 2023) - Tan, Shaojie; Han, Jiarui; Yuan, Xiangnan; Song, Ziyu; Gao, Liheng; Gao, Jing; Wang, Lu
Graphical abstract: Highlights: A facile strategy is proposed to develop pH-responsive fibers of PVA/PAA-epigallocatechin gallate. The membrane can respond to dynamic changes in wound pH and intelligently control the rate of drug release. The membrane is well adapted to the needs of wounds in different stages of healing. The membrane exhibited promising accelerates wound closure process. Abstract: High blood glucose levels, excessive production of reactive oxygen species (ROS), unbalanced inflammatory responses and impaired angiogenesis render chronic wounds more likely to be colonized by bacteria which can form biofilms, leading to recurrent infections and prolonging disunion. The pH-responsive fibers of poly (vinyl alcohol) (PVA)/poly (acrylic acid) (PAA) -epigallocatechin gallate (EGCG) have been constructed. The fibers were able to swell (pH > 7.4) /shrink (pH < 6.5) reversibly with changes in wound pH, controlling the rate of drug release and thus dynamically modulating the complex inflammatory environment of the wound. At the phase of bacterial infection (pH = 7–9), the polycarboxylic acid groups in the network ionized, and the dynamic hydrogen bond between EGCG and PVA and PAA was broke, triggered an increased release of EGCG (87.4 %). Thereafter, the EGCG cleared excess ROS (greater than80.0 %) from the wound and showed significant antibacterial activity against S. aureus (98 %) and Pseudomonas aeruginosa (96.7 %), inhibited biofilm formation (74 %). At the proliferative phase, the wound switched to acidic (pH ∼ 6.5). Fibers swelled less and tended to shrink. The release of EGCG was slowed down (45.8 %) to promote macrophage polarization and remodel the wound microenvironment.